Pengembangan Dashboard Informasi Gereja Tangguh Bencana dengan Metode User Centered Design - Ebentera Santosa; Kristian Adi Nugraha; Agata Filiana (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
Indonesia is a country prone to natural disasters, from earthquakes to annual flood. These can affect, and even at times, endanger people's lives. JAKOMKRIS PBI or the Christian community for disaster management in Indonesia has the duty to aid with Christian churches and institutions to actualize the concept of disaster-resilient church. One of the ways that can help JAKOMKRIS PBI's main goal is to create a website-based dashboard displaying information related to the concept of disaster-resilient church. This research applies the principles of User-Centered Design which in its development focuses on the user. User-Centered Design requires information about the appearance of the interface desired by the user. The results of the research are expected to be able to assist users in preparing churches for disaster events by providing provisions and disaster risk reduction based on managed data. This research uses usability tests using performance metrics and System Usability Scale (SUS) methods. The performance metrics test results for the efficiency value of 90.95% for the user role and 100% for the admin role, while the effectiveness value is 96% for the user role and 100% for the admin role and the results of the System Usability Scale (SUS) test are 81.5 for the user role and 81.25 for admin roles.